Synthesis, Characterization, Thermal Studies, and Antioxidant Activities of Azo Dye[2-[(3-Hydroxyphenyl)diazinyl]-1,2-Benzothiazol-3(2H)-one-1,1-Dioxide]and Metal Ion Complexes - SH. H., Fatimah Al-zahraa; Al-Hamdani, Abbas Ali Salih (Iraqi Journal of Science, 2024)
The new azo dye was synthesized via the reaction of the diazonium salt form of 3-aminophenol with 2-hydroxyquinoline. This dye was then used to access a series of complexes with the chlorides of manganese, iron, zinc, cadmium, and vanadium sulfate. The prepared ligand and its complexes were characterized by FT-IR spectroscopy, UV-visible spectroscopy, mass spectrometry, thermogravimetric analysis, differential scanning calorimeter, and microelemental analysis. Conductivity, magnetic susceptibility, metal content, and chlorine content of the complexes were also measured. The ligand and cadmium complex were identified using1H NMR and 13C NMR spectroscopy. The results showed that the shape of the ligand is a trigonal planner, and the complex shapes are tetrahedral, except for vanadium, which isa square-based pyramid. Additionally, the findings demonstrated that the complexes include water inside the coordination field and that each and every one of them is a non-electrolyte. The dye used the complexes prepared from it to determine their ability to inhibit free radicals by measuring their ability as antioxidants using DPPH as a free radical.D-ascorbic acid was employed as a standard substance in determining the value of IC50, as it was found that the ligand had a high ability to inhibit free radicals. The ability to inhibit the complexes varied according to the value of IC50, and the results are as follows: H2L ˃ D-ascorbic acid ˃Zn-complex ˃Fe-complex ˃ V-complex ˃Cd-complex ˃ Mn-complex.